UV but not X rays stimulate homologous recombination between sister chromatids and homologs in a Saccharomyces cerevisiae mec1 (ATR) hypomorphic mutant - Fasullo, Michael (2008)
MEC1, the essential yeast ATM/ATR homolog, prevents replication fork collapse and is required for the cellular response to DNA damage. We had previously observed higher rates of spontaneous SCE, heteroallelic recombination and translocations in mec1-21 mutants, which still retain some G2 checkpoint function, compared to mec1 null mutants, which are completely defective in checkpoint function, and wild type. However, the types of DNA lesions that are more recombinogenic in mec1-21, compared to wild type, are unknown. Here, we measured DNA damage-associated SCE, homolog (heteroallelic) recombination, and homology-directed translocations in mec1-21, and characterized types of DNA damage-associated chromosomal rearrangements that occur in mec1-21. Although frequencies of UV-associated recombination were higher in mec1-21, the mutant was defective in double-strand break-associated SCE and heteroallelic recombination. Over-expression of Rad53 in mec1-21 reduced UV-associated recombination but did not suppress the defect in X-ray-associated recombination. Both X ray and UV exposure increased translocation frequencies in mec1-21, but the majority of the UV-associated products were non-reciprocal translocations. We suggest that although recombinational repair of double-stand breaks is less efficient in mec1 mutants, recombinants may be generated by other mechanisms, such as break-induced replication.